Molecular characterization of human adenoviruses in urban wastewaters using next generation and Sanger sequencing. (15th September 2017) - Iaconelli, M.; Valdazo-González, B.; Equestre, M.; Ciccaglione, A.R.; Marcantonio, C.; Della Libera, S.; La Rosa, G.
Abstract: Human adenoviruses (HAdVs) are of major public health importance and are associated with a variety of clinical manifestations, including gastroenteritis, respiratory, ocular and urinary tract infections. To study the occurrence, prevalence and diversity of HAdV species and types circulating in Italy, we conducted a large-scale molecular-epidemiological investigation, a yearlong monitoring of 22 wastewater treatment plants, covering 10 Italian regions, representative of northern, central, and southern Italy. A total of 141 raw sewage samples were collected from January to December 2013, and processed to detect and characterize by phylogenetic analysis a fragment of the hexon coding region of HAdVs. Nested PCR results showed the presence of HAdVs in 85 out of 141 samples (60% of samples). Fifty-nine samples were characterized by conventional Sanger sequencing as belonging to four HAdV species and four types: A (type 12, 5 samples), B (type 3, 8 samples), C (type 5, 1 sample) and F (type 41, 45 samples). The remaining 26 samples could not be characterized because of uninterpretable (mixed) electropherograms suggesting the presence of multiple species and/or types. Pools of characterized and uncharacterized PCR amplicons were further analyzed by next-generation sequencing (NGS). NGS results revealed a marked HAdV diversity with 16 additional types detected beyond the four types found by Sanger sequencing. Overall, 19 types were identified, belonging to HAdV species A-F: types 12 and 31 (species A), type 3 (species B), types 1, 2, and 5 (species C), types 9, 17, 24, 26, 37, 38, 42, 44, 48, and 70 (species D), type 4 (species E), and types 40 and 41(species F). An untypeable HAdV was also detected, showing similar percentages of identity with more than one prototype (types 15, 30, 56, and 59). Our findings documented the circulation of a wide variety of species and types in raw sewage, potentially able to affect other surface water environments and hence human health. Next-generation sequencing proved to be an effective strategy for HAdV genotyping in wastewater samples. It was able to detect a wide range of "less prevalent" types unidentified by conventional Sanger sequencing, confirming that studies based on conventional technologies may grossly underestimate the existence of some, possibly less common, types. Knowledge of the distribution of HAdV species and types would improve our understanding of waterborne HAdV-related health risks. Graphical abstract: Highlights: Next generation (NGS) and Sanger sequencing to detect human adenovirus in wastewater. NGS able to detect types unidentified by conventional Sanger sequencing. A wide variety of human adenovirus species and types detected in raw sewage.